A comparative study on guide access and ultrasonic access for fiber post removal - GE Bing, HUANG Lumei, ZHU Wenwei, ZHU Ye, WU Yumin, CHEN Chen (Kouqiang yixue)
Objective To compare the advantages and disadvantages of two fiber post removal methods, guide-supported and ultrasound assisted, for the removal of fiber posts in molars using in vitro experiments. Methods Twelve human extracted molars were randomly divided into a guide group and an ultrasound group for root canal treatment and fiber post restoration. The fiber posts were removed using digital guide and ultrasound instruments, respectively. The time of removal of fiber post and the degree of tooth tissue damage was compared between two groups. Results The operation time for each tooth in the ultrasound group was (11.14±1.62) minutes, while that in the guide group was (5.40±0.90) minutes. The ultrasound group had a significantly longer duration than the guide group, and the degree of crown damage to dental tissue was also significantly higher than that of the guide group. Conclusion Removing fiber posts with the support of guide can shorten clinical operation time, reduce technical sensitivity, and preserve remaining dental tissue as much as possible.